Methods Employed in Monitoring and Evaluating Field and Laboratory Systems in the ANISA Study: Ensuring Quality - Connor, Nicholas E; Islam, Mohammad Shahidul; Arvay, Melissa L; Baqui, Abdullah H; Zaidi, Anita K; Soofi, Sajid B; Panigrahi, Pinaki; Bose, Anuradha; Islam, Maksuda; El Arifeen, Shams; Saha, Samir K; Qazi, Shamim A (The Pediatric infectious disease journal, 2016)
The Aetiology of Neonatal Infection in South Asia (ANISA) study maintains operations in Bangladesh, India and Pakistan. We developed and deployed a multilayered monitoring system to measure performance indicators of field sites and laboratory operations. This system allows for real-time provision of feedback to study site teams and project stakeholders. The goal of this monitoring and evaluation system is to promote optimal performance and consistency in protocol application at all sites over the course of the study, thereby safeguarding the validity of project findings. This article describes each of the interdependent monitoring layers that were conceptualized, developed and employed by the ANISA coordination team. Layers of monitoring include site-level, central and database-related activities along with periodic site visitation. We provide a number of real-world examples of how feedback from the ANISA monitoring system directly informs a number of crucial decisions and course corrections during the project. The ANISA monitoring system represents a transparent, understandable and practical resource for development of project monitoring systems in complex multisite health research projects.